Parvovirus in the Second Trimester: A Case of Unremitting Fetal Anemia [34G]. (May 2020) - Roser, Brittany; O'Hara, Shaelyn; Stone, Joanne L.
Abstract : INTRODUCTION: Parvovirus B19 has been associated with spontaneous abortion, hydrops fetalis, and stillbirth when acquired in pregnancy.[1] When fetal anemia is diagnosed prenatally, fetuses usually respond to a single transfusion. In surviving neonates, the post-natal course and timeframe for bone marrow recovery is not established. METHODS: A 27 year-old primigravida at 26 weeks gestation presented to her community hospital with decreased fetal movement. Work-up revealed nonimmune hydrops fetalis secondary to Parvovirus B19 infection with +IgM seroconversion, for which she transferred to our center for percutaneous umbilical blood sampling (PUBS) and transfusion. She underwent three PUBS procedures due to persistently elevated MCA Dopplers and Category II tracing prior to presenting in preterm labor at 29 weeks. Upon delivery, the neonate weighed 1490 g, Apgar scores were 4 and 7 at 1 and 5 minutes, and a venous umbilical cord gas pH was 7.45. The neonate was admitted to the NICU for prematurity and required transfusions on day of life (DOL) 0, 18, 32, and 46 for persistent Parvovirus-induced erythroblastopenia. A repeat Parvovirus B19 PCR was greater than 10, 000, 000 copies at DOL 43 prompting IVIG therapy. Blood counts stabilized thereafter. On DOL 73 the neonate was 3100 g and breathing on room air, discharged home without other complications. On DOL 154, the Parvovirus B19 PCR was 70, 350 copies and the infant was doing well at home. CONCLUSION: We present a case of parvovirus infection acquired in the second trimester requiring multiple transfusions, with an unusual post-natal course that has yet to be described.